PENGARUH IKLIM ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI (Studi Pada Perawat RSIA Eria Bunda Pekanbaru) - Rani Puspita Sari; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine how the influence of organizational climate and job satisfaction on organizational commitment (studies on nurse of RSIA Eria Bunda Pekanbaru).This research method is descriptive and quantitative using SPSS 17 program, wherein the samples used are nurse of RSIA Eria Bunda Pekanbaru with respondents as many 76 people. For a sampling technique used census method. The data collection is done through questioners and interviews.The results of the analysis using the validity test, reliability test, determination test, simple linear regression test, multiple linear regression test , t test and F test so it can be seen that variable organizational climate to organizational commitment, that job satisfaction significantly influence organizational commitment, and significant influence between society together climate and job satisfaction on organizational commitment.Keywords: Organizational Climate, Job Satisfaction, Organizational Commitment